Perancangan Perbaikan Proses Bisnis Divisi Layanan Ambulans dan Kemanusiaan pada Lembaga Amil Zakat - Intan Dwi Permatasari; Hardianto Iridiastadi (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2023)
Lembaga Amil Zakat (LAZ) are responsible for managing and distributing alms, zakat, and infaq through programs that spread benefits. One of the programs in channeling funds is the Ambulance and Human Services division which provides non-commercial ambulance services and humanitarian assistance programs. In this study, the Ambulance and Human Services divisions are not the main program of the lembaga amil zakat (LAZ), so the problems that occur are not a top priority to be resolved. These problems include the lack of coordination between field officers, the large number of service cancellations by applicants, errors in analyzing the conditions of beneficiaries, and delays in submitting reports to management. These problems arise because not all parties understand the flow of business processes and there is no set work standard. This study aims to propose business process improvements by evaluating and designing business process improvements in the Ambulance and Human Services divisions of the lembaga amil zakat. The Business Process Improvement (BPI) Framework is used to identify business processes running in agencies. This study identified 7 business processes with risk priorities through risk assessment analysis using the Failure Mode, Effect, and Criticality Analysis (FMECA) method. In addition, through the evaluation of value added assessment, 22 business processes or 29.7% non-value added (NVA), 34 business processes or 45.9% organizational value added (OVA), and 18 business processes or 24.3% were found. is the real added value (RVA). Furthermore, the draft business process improvement proposal is then outlined in the form of a project charter. Two project charter documents were generated, one related to the ambulance service workflow and the other related to the design of the RKA, RAB and financial reports. The results of this research are expected to be a guide for the ambulance and humanitarian services division in improving business processes in order to provide more effective and efficient services